Fashion design education students learning readiness; increase or decrease - Ernawati, Ernawati (Universitas Negeri Padang, 2022)
This study is based on the problem of many students do not have the learning readiness in fashion design education. This study aimed at the influence of pedagogy and learning interest on fashion design education students learning readiness. The total population was 497 students of the Fashion Design Program of Universitas Negeri Padang. The sampling technique used in this study is total sampling. A total of 497 respondents were successfully collected. The data analysis technique used is Partial Least Square Structural Equation Modelling (PLS-SEM). The results showed that: There is a significant effect of pedagogy toward fashion design education students learning readiness and there is a significant effect of learning interest toward fashion design education students learning readiness. What could be said from the result of the study is that good pedagogical abilities of lecturers could be increased fashion design education students learning readiness and high learning interest of students could be increased fashion design education students learning readiness.